2017
DOI: 10.2134/jeq2016.07.0275
|View full text |Cite
|
Sign up to set email alerts
|

Management Options for Contaminated Urban Soils to Reduce Public Exposure and Maintain Soil Health

Abstract: Soil management in urban areas faces dual challenges of reducing public exposure to soil contaminants, such as lead (Pb) and polycyclic aromatic hydrocarbons, and maintaining soil function. This study evaluated three management options for an urban lot in Cleveland, OH, containing 185 to 5197 mg Pb kg and 0.28 to 5.50 mg benzo(a)pyrene kg. Treatment options included: (i) cap the site with a soil blend containing compost and beneficially reused dredged sediments, (ii) mix compost with the soil, and (iii) mix co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The concentration of B[ a ]P was from 0.3 to 0.9 mg/kg of soil. B[ a ]P was also found in the concentration range from 0.28 to 5.50 mg/kg in municipal soil in Cleveland [ 45 ]. In another study, B[ a ]P was determined to be in a mean value of 2.31 ± 1.13 μg/kg in soil from greenhouse crops in the Antalya Aksu region in Turkey [ 46 ] ( Table 3 ).…”
Section: Sources Of Human Exposure To B[ a ]Pmentioning
confidence: 99%
“…The concentration of B[ a ]P was from 0.3 to 0.9 mg/kg of soil. B[ a ]P was also found in the concentration range from 0.28 to 5.50 mg/kg in municipal soil in Cleveland [ 45 ]. In another study, B[ a ]P was determined to be in a mean value of 2.31 ± 1.13 μg/kg in soil from greenhouse crops in the Antalya Aksu region in Turkey [ 46 ] ( Table 3 ).…”
Section: Sources Of Human Exposure To B[ a ]Pmentioning
confidence: 99%
“…Remediation of contaminated sites in urban environments should consider combining risk mitigation with the creation of green spaces. For example, Obrycki et al (2017) evaluated three management options for an urban site contaminated with Pb and PAHs. They found that the soil capping placed over the site reduced surface soil Pb from up to 5149 to 12.4 mg Pb kg −1 and benzo(a) pyrene content from up to 5.50 to 0.99 ± 0.41 mg kg −1 , which reduced human exposure to these contaminants markedly.…”
Section: Urban Green Space and Human Healthmentioning
confidence: 99%
“…These mine wastes are a continuous source of environmental contamination, mainly AMD, which arises from the oxidation of the sulfide wastes, a process which is well-known and has been thoroughly described [14,[34][35][36][37]. Remediation of mine-degraded sites is imperative to reduce the potential risks to the surrounding ecosystems and, consequently, to humans, and a source of continuous AMD formation [109][110][111]. Consequently, these mine waste deposits should be removed and/or controlled.…”
Section: Remediation Of Mine-degraded Sites In the Portuguese Sector ...mentioning
confidence: 99%